Household Economy in the Rural Sector of the Border Region between Ecuador and Colombia and Alternatives to Overcome Poverty - Vallejo, Jaime Rodrigo Moreno; Kerchis, Donald E. (European Journal of Economics and Business Studies, 2019)
This research examines the present-day reality in the rural area on the border between Ecuador and Colombia, focusing on the current situation of the rural women; this study looks at the process of self-awareness, validation and empowerment of these women in this border region. As a consequence, the fundamental objective is to analyze and evaluate the participation and empowerment of rural women and to identify their contribution to alleviate the worst conditions of poverty. This study also examines the ability of these rural women to influence the public policy process and to improve gender equity and quality of life. Rural women are confronted with a wide array of economic, social, political and cultural challenges. These women lack stable employment opportunities; their incomes are variable and depend on a livelihood based upon agriculture and livestock. Their common characteristics include low educational attainment level, gender disparities, relatively higher unemployment rate, exclusion from decision-making circles, lack of opportunity, lack of institutional support, sexism, androcentric domination, inappropriate workplace behavior and domestic violence; All extremely unfortunate outcomes that both derive from and are exacerbated by low income levels and increasing levels of poverty among this rural population.
Keywords: Public Policies, Poverty, Household Agriculture, and Public Partnerships